2021
DOI: 10.1038/s41598-021-91187-2
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone modifies hepatic miRNAs expression in a model of MAFLD/NASH

Abstract: AbstractmiRNAs are involved in the development of metabolic associated fatty liver disease (MAFLD) and nonalcoholic steatohepatitis (NASH). We aimed to evaluate modifications by prolonged-release pirfenidone (PR-PFD) on key hepatic miRNAs expression in a MAFLD/NASH model. First, male C57BL/6J mice were randomly assigned into groups and fed with conventional diet (CVD) or high fat and carbohydrate diet (HFD) for 16 weeks. At the end of the eighth week, HFD mice were divided in two and only one half was treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
(86 reference statements)
3
6
0
Order By: Relevance
“…Similarly, our data showed a higher hepatic miR-34a-5p expression in MAFLD model, while MO administration lessens its induction. In addition, a decrease in the expression of miR-34a-5p and an increase in its target genes Sirt1 and Ppara have been reported when PFD was used against MAFLD development in a rodent model [ 53 ]; these results are in accordance with our data.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, our data showed a higher hepatic miR-34a-5p expression in MAFLD model, while MO administration lessens its induction. In addition, a decrease in the expression of miR-34a-5p and an increase in its target genes Sirt1 and Ppara have been reported when PFD was used against MAFLD development in a rodent model [ 53 ]; these results are in accordance with our data.…”
Section: Discussionsupporting
confidence: 93%
“…It has been demonstrated that the miR-122 expression levels rise in the mouse liver over the course of development, peaking immediately before birth. Therefore, the loss of miR-122 expression in HCC may signify either a reversal of differentiation or a block at a less differentiated state [ 10 , 24 ]. Accordingly, this study was designed as an attempt to restore the normal miRNA expression pattern of an oncogene; miR-221, and a tumor suppressor miRNA; miR-221, that had been disrupted during the process of hepatocarcinogenesis and to explore whether this therapeutic strategy would be more effective than a single miRNA restoration approach.…”
Section: Discussionmentioning
confidence: 99%
“…Functions of miR-34a may differ depending on liver diseases, animal models, or the kinds of liver cells. 20 Similarly, acute attenuation of angiogenesis is good for ALD but may have dire consequences in the future. Since hepatic cells communicate with each other and orchestrate to maintain liver homeostasis during liver injury, miR-34a could play a vital role only in specific liver cells, such as hepatic macrophages and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%